Adaptive local searching and caching strategies for on-demand routing protocols in ad hoc networks. (10th July 2006) - Cheng, Zhao; Heinzelman, Wendi B.
On-demand routing protocols are widely used in mobile ad hoc networks due to their capability of adjusting to frequent network topology changes within acceptable routing overhead. In this paper, we reinvestigate two techniques, route caching and searching localisation, in particular their joint effect on reducing routing overhead. We first analyse and present the optimal value for two essential parameters: route caching validation probability and local searching radius. We then propose a new routing strategy that adapts to the current caching availability and is self-tunable towards the optimal performance. Simulation shows that routing overhead is thus greatly reduced.